Building social capital in a new home country. A closer look into the predictors of bonding and bridging relationships of migrant populations at different education levels - Tuominen Minna; Kilpi-Jakonen Elina; García-Velázquez Regina; Castaneda Anu; Kuusio Hannamaria (Turun yliopisto, 2023)
This paper explores factors that may facilitate or hinder the development of migrant populations’ social capital in a settlement country. As earlier research has shown that higher educated migrants tend to form more extensive social relationships, we explore whether there are differences between tertiary educated migrants and those with lower education levels in terms of the background characteristics that predict their social capital composition. The study builds on Robert Putnam’s dyad of bonding and bridging social capital, which are here combined into a single dependent variable. Multinomial regression analyses are done separately for the two education groups. Our data comes from the Survey on Well-Being among Foreign Born Population in Finland (n: of 5,247). The study finds important differences between the education groups both in terms of social capital composition and the respective predictors. Among those with higher education, abundant social capital (i.e. extensive bonding and bridging relationships) is the most common composition, while in the lower education group, the proportion of people with scarce social capital (limited bonding and bridging relationships) outnumbers those with abundant capital by more than twofold. Both education groups draw from similar resources to build abundant social capital, a satisfactory level of income emerging as the single most important underlying factor. However, a satisfactory income level is by far a more common feature in the higher education group. Additionally, the higher education group draws from a more diverse set of other migration and context-related factors to prevent scarce or one-sided social capital.